Jackson students practice first aid, 1941 - Munro, Melville S. (Tufts Archival Research Center, 2005)
5x7 in Munro Scrapbook v. 74, p. 16; Jackson Students apply practical first aid after completing a 10 weeks course given by the Red Cross